Analisis Penggunaan Bahasa Indonesia yang Baik dan Benar di SDN 065013 - Nadia Kezia Situmeang; Sri Wenni; Sardame Hotmauli Sitompul; Hendra Kurnia Pulungan (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research aims to analyze the use of good and correct Indonesian in various domains of Indonesian society. The use of good and correct Indonesian is an important aspect in maintaining diversity and strengthening national identity. However, there are still many deviations and errors in the use of Indonesian, both in oral and written communication.